Degradação de cloranfenicol por fotocatálise heterogênea em diferentes matrizes aquosas: avaliação dos parâmetros operacionais, toxicidade e identificação dos produtos de transformação - Marson, Eduardo Oliveira (2018)
It is known that conventional water and sewage treatment plants have not been projected to eliminate contaminants of emerging concern, such as antibiotics. In this context, among the advanced oxidation processes, heterogeneous photocatalysis was evaluated as an alternative for the treatment of different aqueous matrices (deionized water, river surface water and sewage treatment plant effluent- STP) containing the antibiotic Chloramphenicol. For this, the operational parameters TiO2 photocatalyst concentration, reaction medium pH and addition of H2O2 were optimized for each matrix in a univariate manner, using as a response factor the antibiotic concentration. In deionized water, for the degradation of 3 µmol L-1 of the compound, the process was efficient in a short time of UV-A radiation (30 min), when applied 100 mg L-1 of photocatalyst at pH 5.70 (natural of the solution). The H2O2 addition, on the other hand, caused an antagonistic effect, which can be explained by the low target compound concentration, and the photocatalyst surface modification, so making this reagent a hydroxyl radical sequester. For 20 µmol L-1 of the compound and 180 min of radiation, 71% of mineralization was obtained, and 9 transformation products were identified by mass spectrometry, which showed no toxicity to Vibrio fischeri bacteria. The application of the process in real aqueous matrices showed the need of longer reaction time application, due the presence of interferers in the composition of these effluents (dissolved organic matter, inorganic ions- SO42¯, Cl¯, NO3¯, NH4+, CO32¯, HCO3¯, among others). At river surface water, 120 min of reaction and 250 mg L-1 of TiO2 was found as an optimal condition, and the H2O2 addition resulted in synergism, because of more hydroxyl radicals produced for the degradation of the target compound and organic matter present. At STP effluent, even with a greater contribution of the photolysis process, 240 min of reaction and 150 mg L-1 of photocatalyst were necessary to obtain a satisfactory efficiency. The addition of H2O2 didn’t provide better degradations, because this reagent competes for the photocatalyst’s active sites with inorganic ions of the matrix, as well as forms less reactive radicals. However, even though in both matrices the experiments showed low toxicity for the Vibrio fischeri bacteria, there was inefficient mineralization, indicating the need to apply longer reaction time. Soon, heterogeneous photocatalysis is efficient for the degradation of Chloramphenicol, but the aqueous matrix to be treated must be considered, since it can strongly influence the process.